Phytochemical Quantification and Efficacy of Persea Americana Extracts on some Selected Pathogens - Sunday Olusegun Oladoye; Victoria Adeola Falade; Adewusi John Adepoju; Geshin John Ibikunle (Faculty of Pharmacy, Universitas Gadjah Mada, 2022)
Medicinal and aromatic plants are increasingly becoming the focus of many researchers in the search for alternative antimicrobial agents due to their large number of diverse bioactive compounds called phytochemicals. Persea americana (Avocado) is an evergreen tree plant known for its healthy fruit and has been used in the management of disease and infections. The stem bark of P. americana was investigated for its phyto-constituents and antimicrobial activity using standard methods. The stem bark was preponderant in polyphenolic compounds of which flavonoid was found to be abundant (480.01), the antimicrobial activity study of the extracts also showed good inhibitory activity on all the tested strains with K. oxytoca (27.50 ± 0.67 mm) and A. flavus (88.89%) mostly susceptible in a concentration-dependent manner. The study revealed that P. americana extracts could be explored in the search for alternative antimicrobial agents.